Life Post-SSEAYP: delving the concept of “SSEAYP Sick” among former participating youth from the ship for southeast Asian and Japanese youth program - Ireena Nasiha Ibnu; Mohd Yusof Zulkefli (Penerbit Universiti Kebangsaan Malaysia, 2024)
The Ship for Southeast Asian and Japanese Youth Programme (SSEAYP) has been running for 46 years. The Cabinet Office of Japan organises it. This programme aims to foster friendship and mutual understanding between Japanese and Southeast Asian youths. After the Ship for Southeast Asian and Japanese Youth Program (SSEAYP) programme ends, all the former Participating Youths (PYs) will experience a new life adjustment, which is famously known as "SSEAYP Sick". Therefore, this study explores the implications of "SSEAYP Sick" among Former Participating Youths who participated in this program. Additionally, it is crucial to investigate how the SSEAYP programme has affected the PYs.The phenomenological approach is used in this qualitative research technique to comprehend how the PYs feel about a specific phenomenon. Twenty-two informants from ASEAN and Japan were interviewed in-depth to get the data. Thematic transcription was done after a descriptive analysis of the interview material. The study discovered that the PYs viewed this programme as a "bonus" regarding the SSEAYP Sick phenomena. This study's implications have identified three critical causes for the life post-SSEAYP among PYs: culture shock, homesickness, and the intricate process of returning adaptation. In addition, every person possesses unique experiences, thoughts, and viewpoints that have aided their development and moulded them into the people they are today.